Model of systematization in Service- Learning Projects (UIC) - Fuertes Camacho, María Teresa (Historia y Comunicación Social, 2014)
The Service-Learning methodology responds to the needs of social context and promotes academic and social dual mission to be met by the universities. The different phases followed to carry out the projects implemented during the Internships of Education Degree at the Universitat Internacional de Catalunya (UIC) were key to the implementation of generic skills essential for work and for life-long learning.
Keywords: Service-Learning; Internships; social responsibility; skills; teaching education